Tablets in Hungarian Primary Schools: An Empirical Study of Institution-level Application - Czékmán, Balázs; Kocsis, Judit; Abari, Kálmán (Central European Journal of Educational Research, 2021)
The increasing interest in introducing tablets into education as well as many countries’ education policies (see Digital Education Strategy) support the integration of the above-mentioned mobile devices (Mulet, van de Leemput & Amadieu, 2019). Accordingly, several governments are presently procuring or have already supplied a significant number of students with these devices (Tamim et al., 2015). Similar to most international large-scale initiatives, there are remarkable variances in tablet-supported education. The different school conditions (infrastructure, framework, human resources) result in the diversity of technological integration. In our research, in order to learn more about the infrastructural conditions at schools’ institutional levels, with online questionnaires we examined 145 primary schools using tablets in their education. We were looking to answer the following, questions: (1) what kind of infrastructural conditions are characteristic of the different institutions? (2) What kind of differences in infrastructural conditions are there between the schools in different settlements? To sum up the results, we can observe significant differences in the number of tablets, their hardware, accessories and software, along with differences in internet access and the regulation thereof.